Determination of copper and cobalt in different tea samples at trace levels by FAAS after preconcentration with a novel iron PAMAM-OH-encapsulated magnetic nanoparticle as SPE sorbent - Yilmaz, Oezge; Koyuncu, Ikbal (SPRINGERNATURE, 2024)
Environmental contamination caused by heavy metals is a significant global concern. The presented study investigated the efficiency of iron PAMAM-OH encapsulated magnetic nanoparticles (Fe-MNP-G2-OH) as sorbent for the preconcentration of copper and cobalt from tea samples. High metal-chelating ethylenediamine core polyamidoethanol generation-2 (PAMAM-G2-OH) was encapsulated with iron oxide (Fe3O4) to synthesize the sorbent. Limit of detection (LOD) values for copper and cobalt extracted and detected by the developed Fe-MNP-G2-OH -SPE-FAAS method were 0.52 and 1.1 mu g L-1, respectively. There were 230- and 101-fold improvement in detection limits for copper and cobalt, respectively, when compared to direct FAAS measurement. The percent recovery results for the analytes in green and black tea samples ranged from 93 to 107%, with low relative standard deviation (%RSD) values. The synthesis of nanoparticle was carried out through a unique method, which was characterized by thermogravimetric analysis (TGA), scanning electron microscope (SEM), and Fourier transform infrared spectroscopy (FTIR) methods. The analytical results demonstrated the applicability and effectiveness of Fe-MNP-G2-OH nanoparticles on the preconcentration of copper and cobalt from tea samples and the developed method is suitable for the trace detection of heavy metals by FAAS method. To the best our knowledge, this is the first study where copper and cobalt in green and black tea samples were extracted by Fe-MNP-G2-OH adsorbent and precipitation of the adsorbent during its synthesis was carried out in acetone medium rather than aqueous one.
Keywords: Hydroxyl PAMAM dendrimer; Iron magnetic nanoparticle; Flame atomic absorption spectroscopy; Metal adsorption; SPE; SOLID-PHASE EXTRACTION; DENDRIMERS; METAL; ADSORBENT; HG(II); OXIDE; LEAD; FOOD; Chemistry